1978
DOI: 10.1128/aem.35.1.216-218.1978
|View full text |Cite
|
Sign up to set email alerts
|

Catechol and phenol degradation by a methanogenic population of bacteria

Abstract: An anaerobic population of bacteria became acclimated to catechol and phenol in 32 and 18 days, respectively. Evidence from carbon balance measurements indicates that the aromatic ring is cleaved and that the products are stoichiometrically fermentable to methane and carbon dioxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(35 citation statements)
references
References 10 publications
1
33
1
Order By: Relevance
“…The ferulic acid-degrading consortia used for these experiments were enriched from anaerobic sewage sludge [5] and maintained with this aromatic acid as the sole carbon and energy source for 5 yr. A serum bottle variation of the Hungate technique [9] was used for strictly anaerobic cultivation. The anaerobic culture procedures, batch culture monitoring techniques, and anaerobic media composition have been described previously [10]. The cultures were fed 3 mM ferulic acid (30 mM total carbon) monthly.…”
Section: Methodsmentioning
confidence: 99%
“…The ferulic acid-degrading consortia used for these experiments were enriched from anaerobic sewage sludge [5] and maintained with this aromatic acid as the sole carbon and energy source for 5 yr. A serum bottle variation of the Hungate technique [9] was used for strictly anaerobic cultivation. The anaerobic culture procedures, batch culture monitoring techniques, and anaerobic media composition have been described previously [10]. The cultures were fed 3 mM ferulic acid (30 mM total carbon) monthly.…”
Section: Methodsmentioning
confidence: 99%
“…Chmielowski et al (1964) first demonstrated phenol degradation by anaerobic microorganisms. Later, Healy and Young (1978) focused on the significance of acclimation and enrichment of the cultures for phenol degradation. By using granular activated carbon as bacteria attachment media, Suidan et al (1983) successfully treated phenolic compounds using anaerobic fluidized-bed reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Methanogenic degradation of benzoate depends on a syntrophic co-operation of fermentative and hydrogen-oxidizing methanogenic bacteria [8,9], whereas trihydroxybenzoates and trihydroxybenzenes were fermented to acetate in pure culture [10]. To date, methanogenic degradation of mono-and divalent phenols has mainly been investigated by tracer experiments with sediment samples or crude enrichment cultures, and has given no information on the stoichiometry of degradation and the 0168-6496/85/$03.30 © 1985 Federation of European Microbiological Societies organisms involved [11][12][13]. The results suggest that catechol is first converted into phenol, which is further degraded via a reductive pathway [11,14].…”
Section: Introductionmentioning
confidence: 99%